Formulation Of Solid Self-Emulsifying Drug Delivery System Using Mixedtocotrienols As The Model Drug - Lee, You Zhuan (2020)
The present study was conducted to develop and evaluate the formulation of a solid self-emulsifying system for enhancing the oral bioavailability of a poorly water-soluble liquid active compound, namely tocotrienols. A suitable solid carrier with high liquid holding capacity was selected. Various properties of several solid self-emulsifying formulations including emulsification efficiency, emulsion droplet size, desorption and powder flow properties were investigated. A solid selfemulsifying formulation with the desired properties was successfully developed, using magnesium aluminosilicate (Neusilin US2) as the solid carrier, containing 65 to 70% TRF and 30 to 35% surfactants (poloxamer and Labrasol) with sodium lauryl sulphate as wetting agent. The formulation showed good self-emulsification efficiency with stable emulsion formed, demonstrated excellent powder flowability, complete desorption of tocotrienols from carrier, and small emulsion droplet size of 210 to 303 nm. Subsequent in vivo studies using Sprague-Dawley rats showed that the formulation with a combination of surfactants (poloxamer and Labrasol) had a faster rate of absorption compared to using only single surfactant (either poloxamer or Labrasol). In a following in vivo study, the solid self-emulsifying preparation with combined surfactants (D4) showed enhanced oral bioavailability (3.4 to 3.8 times higher) compared to the non self-emulsifying oily liquid preparation when administered at fasted state in rats. The formulation which was in a dry powder form was further developed into a hard gelatin capsule dosage form, containing 100 mg tocotrienols in each capsule.